Música, cognição e desejo: a crítica cultural de Th. Adorno e o dodecafonismo de Schönberg - Felicio Ramalho Ribeiro (2017)
The aim of our study was to understand how Schönbergs music acquires a status of knowledge, which appears under several nuances in Adornos work. We start by investigating the genesis of the identitary instrumental reason in the Dialectic of enlightenment, seeking to establish its relation with the phenomenon of narcissism in Freud. We then analyzed the incorporation of the principles of enlightened racionality by popular music in the culture industry, emphasizing its fetishistic aspect. The third chapter gives an exposition of the characteristics of Adornos negative dialectic demonstrating its contrast with the dialectic of enlightenment. Finally, we try to show the influence of Schönbergs composition in Adornos philosophy, the socio-historical knowledge present in it and the self-knowledge provided to the listener.